Wild dog management: understanding rural landholders' willingness to participate in coordinated control programs. Issue 1 (2nd January 2023) - McLeod, Lynette J.; Hine, Donald W.
ABSTRACT: Wild dogs pose a major threat to agriculture, biodiversity and community health across many areas of Australia. Coordinated actions are considered one of the most effective methods to minimise this threat, yet many landholders fail to engage. We used a mixed methodology, interviewing 14 wild dog experts and surveying 198 landholders to identify and organise potential drivers and barriers to participation in coordinated actions using the Capability, Opportunity, Motivation (COM) Behavioural model. Landholders' willingness to participate in coordinated control was found to be influenced primarily by their awareness of wild dog problems and motivational factors to join a group. However, segmentation using latent profile analysis highlighted that landholders were not a homogenous group, with each of the identified segments exhibiting their own unique COM profile. The use of the COM model and associated Behaviour Change Wheel framework allowed us to recommend the most appropriate type of interventions to enable practitioners to connect and engage with targeted audiences within their own communities.